Toll-like receptor 2 and Toll-like receptor 4 exhibit distinct regulation of cancer cell stemness mediated by cell death-induced high-mobility group box 1 - Xuelian Chen; Fang Cheng; Yanfang Liu; Lirong Zhang; Lian Song; Xiaojie Cai; Tao You; Xin Fan; Dongqing Wang; Aihua Gong; Haitao Zhu (ELSEVIER SCIENCE BV, 2022)
Background: High-mobility group box 1 (HMGB1), a common extracellular damage associated molecular pattern molecule, is overexpressed in several solid tumors including pancreatic carcinoma. We previously observed that radiotherapy induced dying cells secrete HMGB1 and accelerate pancreatic carcinoma progression through an unclear mechanism.Methods: Using the Millicell system as an in vitro co-culture model, we performed quantitative reverse transcriptase-polymerase chain reaction, western blot and sphere forming ability analyses to access the effect of dying-cell-derived HMGB1 on CD133(+) cancer cell stemness in vitro and in vivo. Interactions between HMGB1 and Toll-like receptor 2(TLR2)/TLR4 were studied by co-immunoprecipitation. Western blot and short-hairpin RNA-based knockdown assays were conducted to detect HMGB1 and TLR2/TLR4 signaling activity.Findings: Radiation-associated, dying-cell-derived HMGB1 maintained stemness and contributed to CD133(+) cancer stemcell self-renewal in vitro and in vivo. In overexpressing and silencing experiments, we demonstrated that the process was activated by TLR2 receptor, whereas TLR4 antagonized HMGB1-TLR2 signaling. Wnt/beta-catenin signaling supported the HMGB1-TLR2 mediated stemness of CD133(+) cancer cells.Interpretation: Our results show how irradiation-induced cell death might enhance the stemness of resident cancer cells, and indicate HMGB1-TLR2 signaling as a potential therapeutic target for preventing pancreatic cancer recurrence. (c) 2018 Haitao Zhu. Published by Elsevier B.V.